Draft Annual Plan 2003-04 Volume-II - Planning Commission (Planning Commission, 2003)
Draft Annual Plan 2003-04-Proposed Outlays-Outlay by Major Heads of Development, Draft Annual Plan 2003-04 Proposed Outlay-Scheme-wise allocation, Physical Targets and Achievements, Draft Annual Plan (2003-04) Proposals for Spillover and Ongoing Programmes, Draft Annual Plan (2003-04)-Proposals for Maximising Benefits of Completed Programmes, Draft Annual Plan (2003-04) - Proposals for Prorammes/Projects-New Schemes, Summary Statement Draft Annual Plan (2003-04) Proposals for Programmes/Projects, Statements regarding Externally Aided Projects, Draft Annual Plan (2003-04) - Outlays - By heads of Development - For District Plans, Centrally Sponsored Schemes.
Planning , Statistics and Science and Technology Department
Planning, Statistics and Science and Technology Department